Respuesta :

1. distribute the 3 into the variable and number in the equation
to do this..
2. multiply 3 by x (obtain the answer of 3x)
3. multiply 3 by -2 (obtain the answer of -6)
4. you now have the equation of ‘14 = 3x-6+5’
5. subtract 6 from 5 (obtain the answer of -1)
6. you now have the equation of ‘14 = 3x-1’
7. add one to both sides (cancel out the negative one and make the opposite side of the equation 15 instead of 14)
8. you now have the equation of ‘15 = 3x’
9. divide both sides by 3 (15 and x)
FINAL ANSWER
x = 5
hope this helps:)